Networks at Scale. A Metadata-Based Approach to Detecting Links Between Fanfiction-Communities - Brottrager, Judith; Glawion, Anastasia; Herget, Katharina; Weitin, Thomas (Digital Humanities 2023: Book of Abstracts, 2023)
This contribution demonstrates a metadata-based approach to analyzing user networks of a German-language fanfiction website. Initially divided into clusters based on louvain modularity, the network is further modified to reveal the level of mutual interaction between reader-writers. The links are then categorized by various attributes, including genre and age restriction.<br